Pengaruh Harga dan Testimoni Pelanggan terhadap Keputusan Pembelian pada UMKM Mysha Cake - Nurholis Nurholis; Riyan Hadithya (MAN 4 Kota Pekanbaru, 2026)
The rapid growth of micro, small, and medium enterprises (MSMEs) in Bandung Regency has intensified competition in the home-based food industry, making an understanding of consumer purchasing decisions increasingly important. This study examines the influence of price and customer testimonials on purchasing decisions at Mysha Cake MSME. A quantitative descriptive approach was employed involving 100 respondents selected using the Lemeshow formula. Data were collected through questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics 25. The findings reveal that price has a positive and significant effect on purchasing decisions, whereas customer testimonials do not have a significant partial effect. Nevertheless, both variables simultaneously have a significant influence, explaining 73.8% of the variation in purchasing decisions. These findings indicate that competitive pricing remains the primary determinant of consumer purchasing decisions, while customer testimonials mainly function as a supporting factor in strengthening consumer trust. The study provides practical insights for MSMEs in designing effective pricing and customer engagement strategies.